Divergence in Single Kernel Characteristics and Grain Nutritional Profiles of Wheat Genetic Resource and Association Among Traits - Khalid, Anam; Hameed, Amjad; Shamim, Sadaf; Ahmad, Javed (Frontiers in Nutrition, 2022)
Triticum aestivum is among the few species of crops which has been widely grown as a source of food. For seed quality trait analysis, wheat germplasm (77 genotypes) was collected from Pakistan’s diverse agro-climatic regions. Significant variation (p < 0.05) was observed for tested parameters amongst tested genotypes. Genotypes with maximum protein content i.e.GA2002 (16.5%) and Marvi (16.5%), moisture content i.e. advance line 9244 (11%), starch content i.e. AARI 2011 (54.1%), zeleny sedimentation rate i.e. advance line 2006 (44ml), wet gluten content i.e. advance line 2006 (44%), kernel weight i.e. advance line TC-4928 (41.6±9.5mg), kernel diameter i.e. sassui (2.91±0.32mm), kernel moisture i.e. AUQAB 2000 (11.7±0.4%), Mairaj 2000 (11.7±0.4%) and Barani-83 (11.7±0.3%), hardness index i.e. Punjab 2011(91±39) are concluded as potential candidates to be explored for bakery products and breeding program to improve quality attributes of wheat. Data were also analysed for correlation, agglomerative hierarchical clustering and principal component analysis (PCA). Cluster analysis clustered all genotypes into five different groups. The D2 statistics confirmed maximum diversity of cluster-V genotypes against genotypes of cluster-IV regarding single kernel characteristics whereas, cluster-II genotypes revealed maximum diversity against cluster- III genotypes relating to grain nutritional profile. The contribution of PC-I regarding single kernel characteristics towards variability was highest (48.58%) and revealed positive factor loadings for kernel weight, kernel diameter and kernel moisture while the contribution of PC-I with respect to grain nutritional profile towards variability was highest (59.76%) and showed positive factor loadings for moisture and starch content. Varieties having good quality attributes can be combined by breeders via various breeding methods with the aim of developing high quality wheat in future.